The Performance of Japanese Mutual Funds - Cai, Jun; Chan, K. C.; Yamada, Takeshi (Review of Financial Studies, 1997)
We analyze the performance of Japanese open-type stock mutual funds for the 1981–1992 period. The results show that, regardless of the performance measures and benchmarks employed, most of the Japanese mutual funds underperform the benchmarks by between 3.6% and 10.8% per annum. These funds tend to invest more in large stocks with low book-to-market ratios. But this feature does not explain the underperformance. A potential explanation is the dilution effect caused by inflows of funds. In Japan, a new investor of an open-type fund only pays in the after-tax value of the net asset value. We conduct a bootstrap experiment to assess the magnitude of this dilution effect.